2013
DOI: 10.1002/jbmr.2089
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Calcium to Zoledronic Acid for Improvement of Cortical Bone in an Animal Model of CKD

Abstract: Patients with chronic kidney disease (CKD) have increased risk of fractures, yet the optimal treatment is unknown. In secondary analyses of large randomized trials, bisphosphonates have been shown to improve bone mineral density and reduce fractures. However, bisphosphonates are currently not recommended in patients with advanced kidney disease due to concern about over-suppressing bone remodeling, which may increase the risk of developing arterial calcification. In the present study we used a naturally occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
95
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 43 publications
19
95
1
1
Order By: Relevance
“…In rodents with CKD, calcium treatment increases FGF23 but also lowers PTH. 24 Thus, it is unclear whether the FGF23 lowering is directly mediated by calcium or indirectly 25 The analyses shown here are consistent with observations in rodents that calcium may be involved in the regulation of FGF23.…”
Section: Discussionsupporting
confidence: 75%
“…In rodents with CKD, calcium treatment increases FGF23 but also lowers PTH. 24 Thus, it is unclear whether the FGF23 lowering is directly mediated by calcium or indirectly 25 The analyses shown here are consistent with observations in rodents that calcium may be involved in the regulation of FGF23.…”
Section: Discussionsupporting
confidence: 75%
“…[7][8][9][10] Biochemical measurements taken at the time of euthanasia in this study are consistent with our previous publications in this model. 7,8,11,12 Table 1 shows that the CKD rats had elevated BUN, phosphorus, and fibroblast growth factor 23 (FGF23) compared with normal (NL) rats. However, there was no statistical difference in calcium and potassium concentrations.…”
Section: Assessment Of Ckdmentioning
confidence: 99%
“…The Langendorff heart preparation requires prolonged (2 hours or more) perfusion and thus, alters histology and PCR. Therefore, tissue for histology was analyzed from sections of CKD and NL rats from a previous study, 11 with confirmation from rats that underwent the electrophysiology studies to directly correlate the results to the presence and absence of fibrosis. For real-time PCR and Western blots, we used previously frozen samples from these latter animals 11 and additional samples from previously frozen tissue.…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Nunes has suggested that it is the deranged metabolism of calcium and phosphorus, rather than the intake, which may be promoting CV calcification, particularly in CKD 31 . Animal studies have shown that low calcium intake induces higher nephrocalcinosis and aortic calcium content, while high calcium intake is not generally associated with calcification in health [32][33][34] but in rats with chronic kidney disease (CKD) and secondary hyperparathyroidism calcium supplementation increased arterial calcification 35 .…”
Section: Calcificationmentioning
confidence: 99%